Perfluorochemical Liquid-Adenovirus Suspensions Enhance Gene Delivery to the Distal Lung - Jeffrey A. Kazzaz; Marlene S. Strayer; Jichuan Wu; Daniel J. Malone; Hshi-chi Koo; Thomas H. Shaffer; Jonathan M. Davis; David S. Strayer; Marla R. Wolfson (Pulmonary Medicine)
We compared lung delivery methods of recombinant adenovirus (rAd): (1) rAd suspended in saline, (2) rAd suspended in saline followed by a pulse-chase of a perfluorochemical (PFC) liquid mixture, and (3) a PFC-rAd suspension. Cell uptake, distribution, and temporal expression of rAd were examined using A549 cells, a murine model using luciferase bioluminescence, and histological analyses. Relative to saline, a 4X increase in transduction efficiency was observed in A549 cells exposed to PFC-rAd for 2–4 h. rAd transgene expression was improved in alveolar epithelial cells, and the level and distribution of luciferase expression when delivered in PFC-rAd suspensions consistently peaked at 24 h. These results demonstrate that PFC-rAd suspensions improve distribution and enhance rAd-mediated gene expression which has important implications in improving lung function by gene therapy.